2019
DOI: 10.1155/2019/2643531
|View full text |Cite
|
Sign up to set email alerts
|

Survival Status and Its Determinants among Under-Five Children with Severe Acute Malnutrition Admitted to Inpatient Therapeutic Feeding Centers in South Wollo Zone, Amhara Region, Ethiopia

Abstract: Background. Under nutrition is one of the leading causes of morbidity and mortality in under-five children in developing countries including Ethiopia. In Ethiopia, many children with severe acute malnutrition (SAM) are treated at inpatient therapeutic feeding centers. However, the survival status and its determinants are not well understood. Therefore, the aim of this study was to estimate the survival status and its determinants among under-five children with severe acute malnutrition admitted to inpatient th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
11
24
1
Order By: Relevance
“…At admission, 64.4% of participants showed up with other co-morbidities on top of SAM. Majority of children (64.9%) were hospitalized with marasmus (non-edematous) type of SAM, similar with some recent studies in Ethiopia [1,13,[25][26][27][28][29][30][31] but in contrary to that of Jimma [32], Hadiya, Ethiopia [33] and Uganda [34], which reported edematous type of SAM was highly encountered. This variation might be attributable to the multi-faceted causes of SAM all over the world.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At admission, 64.4% of participants showed up with other co-morbidities on top of SAM. Majority of children (64.9%) were hospitalized with marasmus (non-edematous) type of SAM, similar with some recent studies in Ethiopia [1,13,[25][26][27][28][29][30][31] but in contrary to that of Jimma [32], Hadiya, Ethiopia [33] and Uganda [34], which reported edematous type of SAM was highly encountered. This variation might be attributable to the multi-faceted causes of SAM all over the world.…”
Section: Discussionsupporting
confidence: 86%
“…It is significantly higher than that of Ayder hospital (11) other similar studies from Bahirdar [13,35], Ghana [20] and Yemen [36]. Nevertheless, it is by greater margin below the minimum international standards [15], in comparison with other study findings in Ethiopia [1,8,24,25,[27][28][29][30][31][32] and similar reports from India, Malawi and Uganda [34,[37][38][39] as well. This might be due to the relatively higher rate of transfer out to nearby health facility, which probably would be to prevent patient overload since one of the study area (AKU-CSH) is the only referral hospital in this particular study area.…”
Section: Discussionmentioning
confidence: 57%
“…This is in-line with a study done by Fikrie et al [24]. The median duration of recovery in this study was higher than the median duration of recovery of other Ethiopian studies [16,17,20,26,27,36], but lower than some other studies done at the various stabilization centers in the country [25,30,31]. These variations could be due to differences in…”
Section: Plos Onesupporting
confidence: 90%
“…This is consistent with the minimum international standard set for management of severe acute malnutrition which is <15%. This is also consistent with other similar studies in Ethiopia (21,24) The average length of hospital stay was found out to be 16 days which is consistent with the minimum international standard set for management of severe acute malnutrition (SPHERE standard). The standard recommends an average length of stay of less than 30 days (9) .The finding of the study in this regard is also in line with other analogous studies conducted in Ethiopia (11,18,21).…”
Section: Discussionsupporting
confidence: 91%